Godly kingship in Restoration England the politics of the royal supremacy, 1660-1688 - Rose, Jacqueline, 1982- (Cambridge ; New York : Cambridge University Press, 2011)
"The position of English monarchs as supreme governors of the Church of England profoundly affected early modern politics and religion. This innovative book explores how tensions in church-state relations created by Henry VIII's Reformation continued to influence relationships between the crown, Parliament and common law during the Restoration, a distinct phase in England's 'long Reformation'. Debates about the powers of kings and parliaments, the treatment of Dissenters and emerging concepts of toleration were viewed through a Reformation prism where legitimacy depended on godly status. This book discusses how the institutional, legal and ideological framework of supremacy perpetuated the language of godly kingship after 1660 and how supremacy was complicated by the ambivalent Tudor legacy. It was manipulated by not only Anglicans, but also tolerant kings and intolerant parliaments, Catholics, Dissenters and radicals like Thomas Hobbes. Invented to uphold the religious and political establishments, supremacy paradoxically ended up subverting them"--
Introduction: the Restoration, the Reformation, and the royal supremacy -- 1. Foundations and legacies: the Reformation and the royal supremacies, 1530-1660 -- 2. The crown and the cavalier Anglicans: prerogative, parliament, and ecclesiastical law -- 3. Spiritual authority and royal jurisdiction: the question of bishops -- 4. Dissenters and the supremacy: the question of toleration -- 5. Anticlericals and 'Erastians': the spectre of Hobbes -- 6. Catholics and Anglicans: James II and Catholic supremacy -- Conclusion.
Includes bibliographical references (p. 284-311) and index.
Description based on print version record.
Keywords: Church and state -- Great Britain -- History -- 16th century; Church and state -- Great Britain -- History -- 17th century; Henry -- VIII, -- King of England, -- 1491-1547 -- Influence; Great Britain -- Church history -- 16th century; Great Britain -- Church history -- 17th century; Great Britain -- History -- Restoration, 1660-1688.; Great Britain -- History -- Stuarts, 1603-1714.; HISTORY / Europe / Great Britain; RELIGION / Christian Life / Social Issues; RELIGION / Christianity / General; Electronic books